2011
DOI: 10.1016/j.jvs.2011.05.112
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous thoracic endovascular aortic repair and endovascular aortic repair is feasible with minimal morbidity and mortality

Abstract: Combined TEVAR and EVAR can be performed successfully with minimal morbidity and mortality. In particular, in this limited series of eight patients, there have been no occurrences of lower extremity paralysis or renal failure despite a high proportion of emergent cases. When anatomically feasible, simultaneous TEVAR and EVAR can be considered as a viable alternative to staged or hybrid repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 19 publications
0
16
0
1
Order By: Relevance
“…2,3 Uncertainty around MAD treatment strategy has been generated by the conflicting data published so far ( Table 5). [5][6][7][8][9][18][19][20][21][22] Two recent articles showed that TEVAR could increase the occurrence of SCI in patients with a history of abdominal aortic aneurysm repair by approximately 7-to 14-fold. 5,6 On the contrary, Martin and colleagues 7 reported that a prior abdominal aortic aneurysm repair, per se, was not significantly associated with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Uncertainty around MAD treatment strategy has been generated by the conflicting data published so far ( Table 5). [5][6][7][8][9][18][19][20][21][22] Two recent articles showed that TEVAR could increase the occurrence of SCI in patients with a history of abdominal aortic aneurysm repair by approximately 7-to 14-fold. 5,6 On the contrary, Martin and colleagues 7 reported that a prior abdominal aortic aneurysm repair, per se, was not significantly associated with SCI.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Kirkwood et al 15 reported eight patients who underwent simultaneous T&E. Four of these patients were treated emergently, but no mortality or permanent paraplegia events were reported. Only one patient in their series had a temporary paraparesis, which was resolved with blood pressure augmentation.…”
Section: Discussionmentioning
confidence: 99%
“…1114 The integration of endoluminal therapies into the surgical management of this unique cohort of patients has resulted in the description of various permutations of staged or simultaneous hybrid treatment strategies. 10,12,15 …”
mentioning
confidence: 99%
“…Surgical repair, though the gold standard, is associated with high morbidity and mortality [1]. Endovascular repair, though widely used for isolated TAA or AAA, has not been well established when both are concurrently present [2,3]. We report simultaneous endovascular repair of two extensive aneurysmal segments in a patient, one involving the distal aortic arch and descending thoracic aorta, and the other involving the infra-renal abdominal aorta and right common iliac artery (CIA).…”
Section: Introductionmentioning
confidence: 99%
“…In-hospital mortality with hybrid treatment for combined TAA and AAA in three reported series using staged or concurrent treatment strategies has ranged from 6 to 17%[2,4,5]. In contrast, no mortality and minimal morbidity was reported in two series using purely endovascular treatment for combined TAA and AAA; in the first of these, Aguiar Lucas et al[2] performed mainly staged treatment in 21 patients, whereas in the second Kirkwood et al[3] performed simultaneous treatment in eight patients. Simultaneous and purely endovascular treatment of combined TAA and AAA therefore seems an attractive option, not only because of low mortality and morbidity, but also because of convenience to the patient and the need to obtain large diameter aortic access once rather than twice.A significant problem associated with extensive stentgraft coverage of the aorta is spinal cord ischaemia, and key to preventing it is the preservation of LSCA and hypogastric artery blood flow.…”
mentioning
confidence: 99%